UJI AKTIVITAS PENURUNAN KADAR GLUKOSA EKSTRAK DAUN BAYAM MERAH (Amaranthus tricolor L.) SECARA IN VITRO - Yulia, Ita Rahma Putri; Anggraini, Devina Ingrid (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2024)
Red spinach leaves are a plant that is rich in fiber and antioxidants which can be used to lower blood glucose levels. Some secondary metabolites that play a role include flavonoids and phenols. The aim of this research was to determine whether red spinach leaf extract (Amaranthus tricolor L) has the potential to lower glucose levels in vitro and to determine the EC50 value of red spinach leaf extract (Amaranthus tricolor L) which can reduce glucose levels. Qualitative analysis shows that red spinach leaf extract contains flavonoids and phenols. Quantitative analysis was carried out using UV-Vis spectrophotometry at a wavelength of 744 nm and an operating time of 25 minutes. Based on the data obtained, it shows that red spinach leaf extract has the potential to reduce glucose levels with an EC50 value of 11.0069 ppm.